Notas nomenclaturais em Salacioideae (Celastraceae) - Lombardi, Julio Antonio [UNESP] (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2010)
Four new combinations are proposed for the following South American Salacioideae (Celastraceae): Peritassa myrsinoides (A.C.Sm.) Lombardi, P. nectandrifolia (A.C.Sm.) Lombardi, P. petiolata (A.C.Sm.) Lombardi, and Tontelea passiflora (Vell.) Lombardi.

São propostas para Salacioideae (Celastraceae) sul-americanas quatro novas combinações: Peritassa myrsinoides (A.C.Sm.) Lombardi, P. nectandrifolia (A.C.Sm.) Lombardi, P. petiolata (A.C.Sm.) Lombardi e Tontelea passiflora (Vell.) Lombardi.
Nomenclatural notes on Salacioideae (Celastraceae)
Keywords: Brazil; Celastraceae; Peritassa; Tontelea; Brasil; Celastraceae; Peritassa; Tontelea